2020
DOI: 10.1111/scs.12910
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with improvement in depressive symptoms among older persons after hospitalisation – a prospective design with two follow‐ups

Abstract: Background Depression is a common disorder in old age and increases with hospitalisation. The aim was to investigate whether improvement in depressive symptoms after hospitalisation is associated with education level, age, gender, living situation, self‐efficacy, activities in daily living and quality of life by (1) examining the prevalence of depressive symptoms at baseline and at 1st and 2nd follow‐up (2) examining different factors’ association with depressive symptoms at baseline and (3) examining differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Possible scores range from 14 to 100, with higher scores indicating better QOL. The LSQ has been used with older adults in Sweden (Roos et al, 2016; Sjölund et al, 2021) and the LSQ‐Chinese version showed acceptable validity and good internal consistency when used with older adults. Cronbach's alpha values were 0.77–0.86 and 0.93 for the factors and total scale, respectively (Lou et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Possible scores range from 14 to 100, with higher scores indicating better QOL. The LSQ has been used with older adults in Sweden (Roos et al, 2016; Sjölund et al, 2021) and the LSQ‐Chinese version showed acceptable validity and good internal consistency when used with older adults. Cronbach's alpha values were 0.77–0.86 and 0.93 for the factors and total scale, respectively (Lou et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…One limitation is that the LSQ was initially developed to measure QOL in women with cancer [ 14 ]. However, it has subsequently been used among the general population [ 14 , 15 ], older people living in nursing homes [ 16 ], and in the community [ 17 ]. Based on its domain, we considered the LSQ a suitable instrument for evaluating QOL among older people in nursing homes.…”
Section: Introductionmentioning
confidence: 99%